Studi Perencanaan Struktur Balok dan Kolom pada Rencana Gedung Fakultas Teknik UNIMUDA Sorong - Arsyi Qodriyanto; Andi Rahmat; Eko Tavip Maryanto (CV. Shofanah Media Berkah, 2026)
The Faculty of Engineering at Universitas Muhammadiyah Sorong requires a new building due to increasing academic activities and the growing demand for classrooms, laboratories, and supporting facilities. Since the campus is located in a disaster-prone area influenced by the Sorong fault and the Papua seismic zone, the structural design of the building must incorporate earthquake resistance. This study proposes a building design utilizing a Special Moment Resisting Frame (SMRF) system to provide ductility and resistance against lateral loads. The analysis results indicate that the required structural elements consist of columns measuring 100 cm × 100 cm and beams measuring 70 cm × 100 cm. The spatial distribution of the building is planned based on its elevation, as well as vertical and horizontal zoning plans, to arrange the space on each floor. Considering that the construction site is situated within the Sorong fault zone and the analysis demonstrates that the structure successfully meets the building performance requirements for both lateral and vertical loads, the SMRF system is considered the most suitable structural solution for the Faculty of Engineering Building.